Effect of Induced Mutation on Pathogenicity Index of Avian Influenza Virus Subtype H7N3 - Khanum, Sofia; Naeem, Khalid; Ahmed, Zaheer; Sattar, Sadia; Hameed, Abdul (International Journal of Poultry Science, 2008)
Intravenous pathogenicity index (IVPI) of three Avian influenza virus (AIV) isolates of serotypes H7N3 was determined at their zero, 10 ,20 and 30th in ovo-passage levels to check the effect of mutation during passage on pathogenicity of the virus. For this purpose three local field isolates of AIV H7N3 were passaged in 9 day old chicken embryonated eggs. Each passaged isolate was subjected to biological evaluation at every 10th passage level. It was found that in-ovo passaging of viruses had both positive and negative effect on pathogenicity index of H7N3 isolates. It was also determined that among three isolates only one isolate showed increase in pathogenicity by passaging while the other two showed decline in their pathogenicity index. On the other hand repeat passaging helped to increase HA titers in all the isolates.